CBMT-36. INITIAL EXPERIENCE WITH HYPERPOLARIZED [2-13C]PYRUVATE MR IMAGING IN PATIENTS WITH IDH-MUTANT GLIOMA. (11th November 2019) - Autry, Adam; Chung, Brian; Chen, Hsin-Yu; Gordon, Jeremy; Lafontaine, Marisa; Chang, Susan; Villanueva-Meyer, Javier; Larson, Peder; Vigneron, Daniel; Li, Yan
Abstract: INTRODUCTION: Hyperpolarized (HP) carbon-13 MR imaging allows for real-time non-invasive measurement of metabolism. Using HP [2- 13 C]pyruvate as a molecular probe enables the measurement of both aerobic glycolysis ([2- 13 C]lactate) and oxidative metabolism (such as [5- 13 C]glutamate and [5- 13 C]glutamine). This study presents the initial patient experience of acquiring HP [2- 13 C]pyruvate MR spectroscopic data. METHODS: Two patients who presented with IDH -mutant gliomas (43 year-old male, grade II astrocytoma, RT/TMZ; 33 year-old female, grade III oligodendroglioma, no RT/TMZ) considered radiologically stable post resection were imaged using a 2D chemical shift imaging (CSI) sequence (15.6–18.8cm 3 spatial resolution, 20s acquisition), following injection of 0.43mL/kg of 250mM HP [2- 13 C]pyruvate. HP [2- 13 C]pyruvate, [5- 13 C]glutamate, [5- 13 C]glutamine, and [2- 13 C]lactate resonances were quantified within a lesion voxel and contralateral normal-appearing voxel. The proton images were aligned to HP data enabled quantification of apparent diffusion coefficients (ADC), perfusion peak height (PH), and MR spectroscopy choline-to-N-acetyl-aspartate indices (CNI). ADC (nADC) and PH (nPH) values were normalized by the median value in normal-appearing white matter. RESULTS: Proton exams revealed no Gd-enhancement lesions. For the T2-hyperintense lesion (T2L), volumeT2L =18.4/4.2cc (Patient#1/Patient#2); median ADCT2L =1.86/1.64; max CNIT2L =3.2/6.5; 90th percentile nPHT2L =1.09/2.11. HP data displayed maximum signal-to-noise ratios (SNR) for [2- 13 C]pyruvate, [5- 13 C]glutamate, [5- 13 C]glutamine, and [2- 13 C]lactate of 1360, 44, 27, and 400, respectively. The HP CSI data contained 15.9/13.7 %T2L; 15.1/4.1 %NAWM; 15.7/22.0 %GM (Patient#1/Patient#2) in selected lesion voxels, while contralateral voxels had %NAWM:%GM of Lesions demonstrated a reduced HP glutamate/pyruvate ratio [#1: 0.0089/0.0102 (lesion/normal voxel); #2: 0.0170/0.0269] and an elevated HP glutamate-to-glutamine ratio in both patients [#1: 0.81/0.66; #2: 0.84/0.66]. DISCUSSION: This first patient experience with HP [2- 13 C]pyruvate showed adequate SNR for quantifying HP [2- 13 C]pyruvate, [5- 13 C]glutamate, [5- 13 C]glutamine, and [2- 13 C]lactate resonances. Future studies will optimize imaging protocols and expand the patient cohort to evaluate aberrant metabolism related to IDH -mutant tumor.